Caspofungin versus amphotericin B treatment of Aspergillus fumigatus in kidneys of chronically immunosuppressed infected mice. Issue 4 (July 2005) - Hickey, Emily; Abruzzo, George; Bowman, Joel; Douglas, Cameron; Gill, Charles; Liberator, Paul; Misura, Andrew; Pikounis, Bill; Bartizal, Ken
Background: Caspofungin acetate has been approved for use in empirical therapy of presumed fungal infections in febrile, neutropenic patients, candidemia, esophageal candidiasis and invasive aspergillosis in patients who cannot tolerate or respond to other therapies. While caspofungin has been studied extensively in mouse survival models of aspergillosis, no study to date has documented the time or dose required to eliminate the detectable Aspergillus fumigatus fungal burden in the kidney of an established mouse infection model.Aim: The goal of this study was to determine the duration of treatment and dose of caspofungin required to reduce the A. fumigatus burden to the limit of detection in kidneys of challenged, immunosuppressed mice.Materials & methods: Dosing was initiated 24 h after infection, and amphotericin B (AmB) was used as a comparator. Immunosuppressed mice were infected intravenously with A. fumigatus and treated intraperitoneally for 14 days with caspofungin (1 or 2 mg/kg), AmB (0.5 mg/kg), or vehicle. Both survival and fungal burden in kidneys were assessed in cohorts by histologic and quantitative polymerase chain reaction analysis.Results: There were no survivors among infected, vehicle-treated mice by day 10 after challenge. At day 42 after challenge in the survival arm of the study, 60% of the mice treated with 2 mg/kg caspofungin, 50% treated with 1 mg/kg caspofungin and 30% treated with 0.5 mg/kg AmB survived. The overall trends for reduction of the kidney burden were similar between quantitative polymerase chain reaction and histologic exam. A total of 92% of animals in the groups receiving caspofungin (1 or 2 mg/kg/day) had no detectable evidence of residual infection on day 42, the last day of evaluation.Conclusion: These results indicate that caspofungin dosed at 1 or 2 mg/kg reduced the histologic signs of A. fumigatus and the kidney burden to the limit of detection in chronically pancytopenic mice. Caspofungin was at least as effective as AmB in both the magnitude and the rate of decrease in A. fumigatus kidney burden in this model.